Animal occurrence and space use change in the landscape of anthropogenic noise. (December 2015) - Chen, Hsiang Ling; Koprowski, John L.
Abstract: Habitat fragmentation, destruction, and disturbance are major threats to biodiversity. Global road networks represent one of the most significant human impacts on ecosystems, and a spatially extensive source of anthropogenic disturbance and noise. We developed a novel approach by combining traffic monitoring with noise mapping on the basis of a standardized traffic-noise stimulus generated by controlled vehicle operation to investigate temporal and spatial heterogeneity of traffic noise. We used animal presence or absence, radio-telemetric monitoring of space use, and remotely sensed habitat characteristics with occupancy modeling and spatial analysis to assess influences of distance from roads, habitat characteristics, and traffic noise level on site occupancy and space use of Mt. Graham red squirrels ( Tamiasciurus hudsonicus grahamensis ). Traffic noise had spatially extensive and negative effects on site occupancy. Animal occurrence decreased as traffic noise increased after accounting for distance from roads. Traffic noise levels in animal core home ranges were lower than noise levels within total home ranges. Our study disentangled effects of traffic noise from confounding environmental characteristics and demonstrated the chronic impacts of traffic noise on animal distribution. We highlight the importance of incorporating spatial and temporal heterogeneity of traffic noise at a local scale when investigating effects of anthropogenic noise on wildlife. Highlights: We use occupancy modeling to assess influences of traffic noise on site occupancy by an endangered forest obligate. We use controlled vehicle operation as a standardized traffic-noise stimulus. Occupancy decreased as traffic noise increased after accounting for distance to roads and other environmental features. Traffic noise levels in animal core home ranges are lower than noise levels within total home ranges.